High Frequency Snubber Circuit for SiC MOSFET Module - LUO Jianbo; FAN Wei; PENG Kai (Kongzhi Yu Xinxi Jishu)
During high frequency switching condition, overvoltage caused by the coupling oscillation between distributed parameters(inductance, capacitor) on Silicon Cabide(SiC) device will easily lead to breakdown damage of devices and the generated electromagnetic noise will interfere the normal operation of other parts in converters. It analyzed the mechanism of overvoltage during SiC MOSFET switching, especially the influence of stray inductance on its switching characteristics, and studied its snubber circuit. Small equivalent signal model of impulse switching was achieved based on big signal model of switching system, and thus analyzed the influence that snubber capacitor brought to switching-off overvoltage, issued a selected plan of SiC MOSFET high frequency snubber circuit. Simulation and experimental results validated correction of the analysis conclusion and effectiveness and feasibility of the plan.